Characterization of conformation and interaction of gene delivery vector polyethylenimine with phospholipid bilayer at different protonation state - Choudhury, Chandan Kumar; Kumar, Abhinaw; Roy, Sudip (Biomacromolecules, 2013)
Polyethylenimine (PEI) is a pH sensitive polymer possessing stretched and coiled conformation at low and high pH, respectively. It is an efficient gene delivery agent. Thus, the interaction of PEI with the biomembrane is very crucial to understand the gene delivery mechanism. In this report, we have investigated the structural properties of PEI and bilayer due to the interaction of PEI with lipid molecules. PEI has coil structure at high pH while at low pH it is elongated. The neutral PEI chain predominately settles itself at the bilayer water interface. We do not find any disruption or pore formation on the bilayer due to interaction of neutral PEI chain. PEI at low pH gets elongated due to electrostatic interaction between charges of the protonated sites. This protonated PEI chain interacts with bilayer membrane, which leads to formation of water/ion channel through the membrane. We have analyzed the structure of the channel and water dynamics along the channel.